2022
DOI: 10.1001/jamapediatrics.2022.3072
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Neutralizing Antibody Levels in Children and Adolescents Up to 16 Months After SARS-CoV-2 Infection

Abstract: after infection. The findings also broaden the understanding about less severe clinical disease in younger children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…In contrast, immunity generated by the whole virus would be evidenced to be more robust and long-lasting. In support of this argument, a recent study from Singapore reported a long-lasting antibody response with at least 13 months of longevity following mild COVID-19 disease [ 27 ]. This indicates that a LAV that induces the immune system like a wild-type infection would also provide long-lasting immunity to COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, immunity generated by the whole virus would be evidenced to be more robust and long-lasting. In support of this argument, a recent study from Singapore reported a long-lasting antibody response with at least 13 months of longevity following mild COVID-19 disease [ 27 ]. This indicates that a LAV that induces the immune system like a wild-type infection would also provide long-lasting immunity to COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…Last, seroconversion is an imperfect proxy for measuring disease prevalence because not all persons seroconvert after SARS-CoV-2 infection, and some literature suggests that rates of seroconversion may be lower or that antibody waning after infection may be more rapid for children or those with asymptomatic or mild illness ( 34 38 ). However, because some data on this issue are conflicting, the potential effect on our results is unclear ( 39 ). Similarly, the exact test characteristics over time for the assays used are not well known.…”
Section: Discussionmentioning
confidence: 97%
“…Initial research focused on evaluating testing methods and antibody responses during acute infection and early post-infection [ 6 8 ]. Data from surveillance studies have documented that nucleocapsid antibodies persist in adults up to 41 weeks post-infection [ 3 , 9 , 10 ] however less data exists for children [ 11 18 ], especially data which include antibodies against virus variants. While children rarely experience moderate or severe disease [ 19 ], infections are frequent.…”
Section: Introductionmentioning
confidence: 99%